تقييم جاهزية المؤسسة الجزائرية للحصول على شهادة المسؤولية الاجتماعية - بلقاسم كحلولي، أحلام; بن عزيزة ،صورية (جامعة الوادي University of Eloued, 2025)
This study aimed to evaluate the readiness of Algerian instituation to obtain the social responsibility certification SA 8000, focusing on the SOMIK company as a case study. This was achieved by examining the extent to which the company under study complies with the requirements SA 8000. 53 questionnaire forms were distributed across the company’s departments. The study concluded with a set of finding‚ the most important of which is that the company under study largely complies with the requirement of SA 8000 through its main dimensions: forced labor‚ occupational health and safety‚ freedom of association‚ non-discrimination‚ disciplinary practices‚ workings hours‚ management systems‚ Child labour and wages. However, ‚ there are some shortcomings‚ such as the mandatory nature of overtime work‚ insufficient complaint handling mechanisms‚ and the lack of adequate and comprehensive awareness programs for all employees of the company.
Assessing the readiness of the Algerian entreprise to obtain the social responsibility certification SA 8000: A case study of Skikda industrial maintenance company (SOMIK)
مقال
Keywords: E m p l o y e e s; Over work; Complaint; Awareness programs